Education Of Life Proficiency In History Learning - Assidiqi, Muadz; Joebagio, Hermanu; Sariyatun, Sariyatun (Universitas Sebelas Maret, 2020)
The twenty-first century continues to experience a breakdown in the foundations of society which causes new and worrisome things. The emergence of a pandemic in this century has a consequence that has caused various problems, especially in the field of education. The development of community needs for education services, especially at the senior high school level (SMA) is not following the improvement of the quality of human resources with life skills. This happens because educational services have not been able to carry out face-to-face learning completely. The implementation of distance learning (PJJ), the use of online learning technology, re-orientation of the curriculum, and improving the skills of educators are policies that are taken to overcome these problems. This study uses a literature review method that aims to critically examine ideas, findings, and knowledge of life skills education to analyze and solve educational problems during the Pademi era, especially in history learning.